College Student Satisfaction with Online Learning during COVID-19: A review and implications (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
The purpose of this research is to summarize the studies examining college student satisfaction with online learning, with a focus on those studies investigating the elements of the online courses designed by the instructors who moved face-to-face courses to distance during the COVID-19 pandemic. Research that describes the components in the online course design is included. The review study by Kauffman pointed out that due to individual differences, some students can do well in online courses while other students may not be able to do well in online courses. This review identified elements in the online course design that contribute to student online learning satisfaction and suggests that instructors can proactively help student online learning by modifying online course components.